Empirical Investigation the Relationship between Strategic Orientations and SMEs Performance in Nigeria - Rogo, Halilu Bello; Mohd Shariff, Mohd Noor; Hafeez, Muhammad Haroon (2017)
This study examine the relationship between strategic orientations and SMEs performance in Nigeria. The debate on entrepreneurial orientation and market orientation to firm performance will for a long time remain area of research. The paper sample consists of 3,723 of all the SMEs operating in Kaduna and Sokoto state.Out of which 205 questionnaires were administered to respondents concerning the entrepreneurial orientation and market orientation to SMEs performance, 197 were returned.The number of valid questionnaire is 191. The data were analyze using Partial Least Square Structural Equation Modelling (PLS-SEM) to determining the effect of the variables of the study.The findings of the paper indicated that entrepreneurship development factors: entrepreneurial orientation and market orientation promoting SMEs performance in Kaduna and Sokoto state.The results showed a statistically significant positive influence of both entrepreneurial orientation and market orientation to SMEs performance.The finding provides the government, policy maker and other SMEs’ stakeholders with the important variables of this entrepreneurial orientation and market orientation to SMEs performance in Nigeria. This study also have suggestion for future research direction.